REPRESENTING FINANCIAL DATA STREAMS IN DIGITAL TWIN (DT) TECHNOLOGY OPERATIONS - Muhammad Irfan; Dr Kirshan Kumar Luhana; Atia Bano Memon; Dr Azeem Akhtar Bhatti; Ali Raza (International Journal of Contemporary Issues in Social Sciences, 2024)
This article will explore and critically discuss the extended areas of using DT technology particularly in the management of personal financial affairs. A digital twin can be defined as an existing cybernetic copy of a real-life object, action or process. Recently they have gained much attention because of elements that can help optimize business. This procedure a review of the literature on the use of digital twin technology in personal asset management in this paper, what it is, its strengths and weaknesses, and its applications. Digital twins that represent replicas of urban settings can hence capture, evaluate and manage several areas of urbanism, such as transportation, structures and even services in real time. These emerging trends and opportunities show that the application of the methodology of using the digital twin technology in individual and personal financial management is not limited to purely traditional fields. Thus, in this research, the digital twin concept will be examined in the context of the next evolutionary step of robo-advisors intelligent financial advisors that can facilitate the personalization and optimization of Fin Tech offerings and solutions management. It can also be suggested that the increased value, associated with the management of a user, and the factors promoting his/her well-being will be obtained by users of DT-enabled robo-advisors. This study also offers useful information for deep learning in the reconversion and improvement of robo-advisors for financial products and services, innovative financial advisors equipped with DT features.